Debt Management and the Performance of Small Scale Enterprises in the Kumasi Metropolis of Ghana - Addaney, Michael; Awuah, Samuel Baffour; Afriyie, Akosua (Journal of Asian Business Strategy, 2016)
This study investigated how debt management impacts the performance of small scale enterprises in the Kumasi Metropolis of Ghana. In total, 120 small scale enterprises were interviewed. The study showed that most small scale businesses lacked in-depth knowledge on the issue of debt management. The study further revealed that the major cause of debts among small scale businesses were lack of advice on the business type and finances, lack of knowledge on the type of business and poor methods of keeping financial records. The study therefore recommends that Small scale businesses must hire financial experts to help them manage their businesses through prudent record keeping. Moreover, it argues that small scale businesses should work within their budgets in order to avoid higher expenditure and subsequent incurring of debts which could be detrimental to the running of their business. It posits that financial institutions should strive to give expert advice on business management to their clients.